Application of Humic Acid and Arbuscular Mycorrhizal Fungi to Increase Growth and Yields of Soybean in Ultisol - Rahayu Arraudah; Yudhy Harini Bertham; Hesti Pujiwati; Bambang Gonggo Murcitro; Entang Inoriah Sukarjo (TERRA : Journal of Land Restoration, 2020)
Soybean is one of the most popular food crops for the community, but the needs for soybeans have not been fulfilled by soybean production. To meet the needs of soybeans, it is necessary to intensify agricultural land in Ultisol. This study aims to obtain the optimum concentration of humic acid and dosage of the Arbuscular Mycorrhizal Fungi (AMF) to increase soybean plants' production in Ultisols. This research was conducted from January to April 2020 in Beringin Raya Village, Muara Bangkahulu District, Bengkulu City, at an altitude of 10 m above sea level. The research design used a Randomized Complete Block Design (RCBD) two factors with three replications, arranged factorially in experimental units. The first factor is the concentration of humic acid, consisting of 4 levels: 0, 15, 30, and 45 mL L-1 . The second factor is the dose of AMF, consisted of 3 levels, namely: 0, 2.5, and 5 g plant-1. The results showed that the maximum soybean growth and yield in Ultisols were obtained from the humic acid concentration at 45 mL L-1 at the dose of AMF at 2.5 g plant-1 . The resulting production potential is 1.99 tons ha-1 . The administration of humic acid or AMF independently at this research stage had not yet given a maximum response to the growth and yield of soybean in Ultisol.